Fairness-Aware Prompt Tuning: Selective Prompt Allocation for Bias Reduction in NLP Models (International Journal of Artificial Intelligence Engineering and Systems, 2026)
Prompt tuning has emerged as a parameter-efficient alternative to full model fine-tuning, enabling large language models to be adapted to downstream tasks through learned soft prompts while keeping pretrained weights frozen. Despite its efficiency advantages, the fairness implications of prompt tuning remain underexplored. Standard prompt tuning applies a single prompt uniformly across all instances, implicitly assuming that a monolithic prompt representation can serve all demographic subgroups equally well. This assumption is at odds with extensive evidence that language models amplify societal biases embedded in training data. In this paper, we introduce the concept of fairness-aware prompt tuning through selective prompt allocation, a system-level framework in which inputs are routed to distinct fairness-optimized prompts based on auxiliary signals that capture protected attribute proxies or bias-sensitive features. We analyze the structural trade-offs involved in partitioning the prompt space for fairness, including prompt catalog design, allocation policy learning, and the tension between group fairness and aggregate accuracy. We further examine infrastructure requirements for deploying selective prompt allocators in production pipelines, touching on latency, storage overhead, and the risks of re-identification when conditioning on sensitive attributes. The governance dimension is discussed in terms of regulatory compliance, transparency obligations, and the necessity of auditability in prompt-based adaptation layers. Through cross-domain comparisons with adversarial debiasing, data augmentation, and output calibration methods, we illustrate how selective prompt allocation creates a new operating point in the bias-accuracy landscape. We conclude by identifying challenges related to long-term fairness drift, adversarial prompt manipulation, and sustainable maintenance, suggesting that selective prompt allocation represents a promising middleware approach for fairness injection in large-scale NLP systems without compromising the efficiency gains of prompt tuning.
Keywords: fairness-aware NLP, prompt tuning, selective prompt allocation, bias mitigation, socio-technical systems, language model deployment